2020
DOI: 10.1177/0146621620909893
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Item Preknowledge Using Response Times

Abstract: Benefiting from item preknowledge is a major type of fraudulent behavior during educational assessments. This article suggests a new statistic that can be used for detecting the examinees who may have benefited from item preknowledge using their response times. The statistic quantifies the difference in speed between the compromised items and the non-compromised items of the examinees. The distribution of the statistic under the null hypothesis of no preknowledge is proved to be the standard normal distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 43 publications
3
24
0
Order By: Relevance
“…It can be shown that for this hypothesis‐testing problem, the L T statistic is identical to the Wald test statistic given bytrueτ^scriptC-trueτ^trueC¯Var(trueτ^scriptC)+Var(trueτ^trueC¯)=trueτ^scriptC-trueτ^trueC¯false[iscriptCαi2false]-1+false[itrueC¯αi2false]-1.Sinharay (2019) also showed that under the LNMRT, L T follows the standard normal distribution under the null hypothesis of no item preknowledge, irrespective of the sizes of scriptC and trueC¯.…”
Section: Literature Review: a Model And Some Existing Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…It can be shown that for this hypothesis‐testing problem, the L T statistic is identical to the Wald test statistic given bytrueτ^scriptC-trueτ^trueC¯Var(trueτ^scriptC)+Var(trueτ^trueC¯)=trueτ^scriptC-trueτ^trueC¯false[iscriptCαi2false]-1+false[itrueC¯αi2false]-1.Sinharay (2019) also showed that under the LNMRT, L T follows the standard normal distribution under the null hypothesis of no item preknowledge, irrespective of the sizes of scriptC and trueC¯.…”
Section: Literature Review: a Model And Some Existing Methodsmentioning
confidence: 99%
“…The LRT statistic for testing H0:normalτscriptC=normalτtrueC¯ against H1:normalτscriptCnormalτtrueC¯ is given bynormalΛT=2false[(boldyscriptC|trueτ^scriptC)+(boldytrueC¯|trueτ^trueC¯)-(y|normalτfalse^)false],where, for example, (boldyscriptC|trueτ^scriptC) is the log‐likelihood of the log‐response times of the items in scriptC, computed at normalτfalse^C. Sinharay (2019) showed that when one uses the LNMRT (van der Linden, 2006) for the response times under the hierarchical modelling framework of van der Linden (2007), (boldyscriptC|trueτ^scriptC) can be expressed asfalse(yCfalse|normalτfalse^Cfalse)=false∑iC-12logfalse[2normalπfalse]+logfalse(αifalse)+trueτ^scriptC2false∑i…”
Section: Literature Review: a Model And Some Existing Methodsmentioning
confidence: 99%
See 3 more Smart Citations